Adsorption and Diffusion of Potassium on 2D SnC Sheets for Potential High‐Performance Anodic Applications of Potassium‐Ion Batteries. Issue 18 (24th September 2020) - Rehman, Javed; Fan, Xiaofeng; Laref, Amel; Zheng, W. T.
Abstract: Pertinent electrochemical characteristics based on K‐ion batteries (KIBs) represent a compelling class of electrode materials that may substitute lithium‐ion batteries, owing to their low cost and common abundance. In this paper, the structural, electronic, and electrochemical features of two‐dimensional (2D) material, the so‐called SnC monolayer, is investigated for anode applications employing first‐principle calculations. Pristine monolayer SnC is found to be an indirect band semiconductor with a band gap of 0.91 and 1.73 eV using PBE and HSE06 schemes, respectively. However, holding a small content of K on the T‐site, this 2D material has a semi‐metallic behavior (due to the defect state), while the conductivity is enhanced by undertaking the adsorption of K on the H‐site. As an anode material, monolayer SnC illustrates a low average open‐circuit voltage of 0.415 V for KIBs with a high K storage capacity of 410 mAhg −1 . The low diffusion barrier (0.17 eV) on the surface of SnC sheet conducts fast charge/discharge cycles. Our results indicate that the 2D SnC could be a promising anode material for K‐ion batteries. According to these findings, we recommend that monolayer SnC can serve as expedient material with tunable capacity and high rate performance for next generation K‐ion batteries. Abstract : Proper profile : The appropriate voltage profile with low average open circuit voltage (0.415 V) and the maximum potassium storage capacity (410 mAhg −1 ) depicts the potential usefulness of monolayer SnC. Furthermore, it is found that there is a very low activation barrier of 0.17 eV for potassium diffusion on the SnC surface, which corresponds to fast K migration in the charge/discharge process. These outcomes reveal that 2D SnC could be a promising anode material for potassium‐ion batteries (KIBs).